Cultural and historical sources of modern sport (second message) - Vasyl Sutula (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to reveal the social mechanism of self-development of modern sport. Material & Methods: systematic and historiographical methods were used during the study. Results: In the 19th century, the concept of "sports" expanded significantly compared with the previous historical period. The determining factor that predetermined the main directions of boxing development was its public recognition. It is shown that the essence of the social mechanism of self-development of modern sport. Conclusions: the social mechanism of self-development of sport, as a specific socially significant phenomenon, manifests itself in dialectical unity, on the one hand, the competing activity of people to meet various needs in the use of physical exercises which is aimed at preparing and participating in competitions, but on the other, social assessment of social phenomena which arise on the basis of such activities.